ST2 blockade mitigates peritoneal fibrosis induced by TGF‐β and high glucose - Kim, Yong Chul; Kim, Kyu Hong; Lee, Sunhwa; Jo, Ji‐won; Park, Jae Yoon; Park, Mi‐seon; Tsogbadrakh, Bodokhsuren; Lee, Jung Pyo; Lee, Jae Wook; Kim, Dong Ki; Oh, Kook‐Hwan; Jang, In‐Jin; et al. (Journal of cellular and molecular medicine, 2019)
Peritoneal fibrosis (PF) is an intractable complication of peritoneal dialysis (PD) that leads to peritoneal membrane failure. This study investigated the role of suppression of tumorigenicity (ST)2 in PF using patient samples along with mouse and cell‐based models. Baseline dialysate soluble (s)ST2 level in patients measured 1 month after PD initiation was 2063.4 ± 2457.8 pg/mL; patients who switched to haemodialysis had elevated sST2 levels in peritoneal effluent (1576.2 ± 199.9 pg/mL, P = .03), which was associated with PD failure (P = .04). Baseline sST2 showed good performance in predicting PD failure (area under the receiver operating characteristic curve = 0.780, P = .001). In mice with chlorhexidine gluconate‐induced PF, ST2 was expressed in fibroblasts and mesothelial cells within submesothelial zones. In primary cultured human peritoneal mesothelial cells (HPMCs), transforming growth factor‐β treatment increased ST2, fibronectin, β‐galactosidase and Snail protein levels and decreased E‐cadherin level. Anti‐ST2 antibody administration reversed the up‐regulation of ST2 and fibronectin expression; it also reduced fibrosis induced by high glucose (100 mmol/L) in HPMCs. Thus, high ST2 level in dialysate is a marker for fibrosis and inflammation during peritoneal injury, and blocking ST2 may be an effective therapeutic strategy for renal preservation.